Cognition and learning in diverse settings - Scruggs, Thomas E., 1948-; Mastropieri, Margo A., 1951- (Amsterdam ; Oxford : Elsevier JAI, 2005)
Essential to the treatment of learning and behavioral disabilities is an understanding of the cognitive processes brought into play in educational contexts, how they contribute to problems in learning and behavior, and how these processes might be ameliorated. Equally important is a careful consideration of the setting in which learning takes place, and how it ameliorates, or contributes to, learning and behavioral disorders. In this volume, the role of cognition in learning and behavioral disorders is considered along with investigation of learning in diverse settings, including clinical, special class, and inclusive general education classrooms. In this volume are chapters on such cognitive processes as working memory, spatial learning, and cognition in mathematics. In addition, learning is examined within a variety of setting arrangements, and considers such topics as the context of teacher-student relationships, co-teaching arrangements in inclusive instruction, issues in educational placement, clinically-based interventions for dyscalculia, collaborative teaching relationships in inclusive social studies teaching. This volume includes contributions from internationally recognized experts in the field of learning and behavioral disabilities. The book is intended for interested professionals and practitioners; researchers in learning and behavioral disabilities; and graduate students in psychology, education, and special education, particularly those concerned with the issues of cognition and learning in a variety of instructional contexts.
Working memory and reading disabilities: a selective meta-analysis of the literature / Olga Jerman, H. Lee Swanson -- Mathematical vs. reading and writing disabilities in deaf children: a pilot study on the development of numerical knowledge / Elisabetta Genovese, Rosalia Galizia, Marco Gubernale, Edoardo Arslan, Daniela Lucangeli -- Instructional support employing spatial abilities: using complimentary cognitive pathways to support learning in students with achievement deficits / William E. Gustashaw, Frederick J. Brigham -- High incidence disabilities: placement determinants and implications for instruction and service delivery / Suzette Ahwee Leftwich, Marjorie Montague -- Cognition and learning in inclusive high school chemistry classes / Margo A. Mastropieri, Thomas E. Scruggs, Janet E. Graetz -- Teacher-student relationships and early school adjustment / Panayota Mantzicopoulos -- Evaluation of inclusion of students with disabilities: integration of different methods / Giulia Balboni, Simona de Falco, Paola Venuti -- Establishing and maintaining collaborative relationships between regular and special education teachers in middle school social studies inclusive classrooms / Cynthia Young Buckley -- Education and treatment of calculation abilities of low-achieving students and students with Dyscalculia: whole class and individual implementations / Daniela Lucangeli, Patrizio Tressoldi, Chiara De Candia -- Inclusive practices in content area instruction: addressing the challenges of co-teaching / Margo A. Mastropieri, Thomas E. Scruggs, Janet Graetz, Nicole Conners -- Misconceptions about history: reflections on teaching for historical understanding in an inclusive fifth-grade classroom / Ralph P. Ferretti, Charles D. MacArthur, Cynthia M. Okolo.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Learning disabled children -- Education; Special education; Inclusive education; Cognition in children; Educational psychology; Learning; Education -- Educational Psychology